Nursing students’ views on individuals with disabilities in disaster situations: A Qualitative Study - Çiğdem Müge Haylı; Ramazan Karataş; Seockhoon Chung; Erkan Kurnaz; Dilek Demir Kösem (Acta Scientiarum. Health Sciences)
This study qualitatively determines the views of nursing students toward individuals with disabilities in disaster situations. Qualitative data were collected between January 18 and April 30, 2024. The study group consisted of 1st and 2nd class nursing program students at Hakkari University Faculty of Health Sciences in Turkey. To determine the students’ views on individuals with disabilities in disaster situations, focus group interviews were conducted; data collection was completed for 35 students, after which data saturation was reached. Sociodemographic data and semi-structured individual interview questions were used to determine the aforementioned views of nursing students. A descriptive/thematic approach was used to analyze the data, and coding and analysis were performed using the MAXQDA qualitative data analysis program. The interviews revealed six main themes: ‘Unique Characteristics of Individuals with Disabilities,’ ‘Self-Efficacy,’ ‘Social/Emotional/ Psychological Attitudes,’ ‘Communication/ Alternative Communication,’ ‘Social Factors,’ and ‘Safety and Treatment.’ Disaster situations negatively impact individuals with disabilities. In addition to determining nursing students’ views on such individuals during disasters, our results can provide help and support.